OPEN ALL NIGHT LONG: The Dark Side of Stomatal Control - Costa, J. Miguel (Plant Physiol, 2015)
Isolation of Arabidopsis mutants that maintain stomata open all night long credits the existence of dedicated regulators for stomatal closure in darkness.